A Strength-based Approach to Exploring Factors that Contribute to Resilience Among Children and Youth Impacted by Disaster. (11th May 2021) - McDonald-Harker, Caroline; Drolet, Julie; Sehgal, Anika
Abstract : Children and youth are commonly viewed as vulnerable during times of disaster. However, research is increasingly uncovering the various ways that children and youth can and do demonstrate resilience when faced with the challenges of disaster. Based on research conducted with 83 children and youth (5 to 17 years) who experienced the 2013 flood in Alberta, Canada, this article discusses the factors that contribute to resilience in this disaster-affected population. A mixed-methods approach was used– the Child and Youth Resilience Measure (CYRM-28) was administered, and in-depth qualitative interviews were conducted with child/youth participants to examine the individual, caregiver, and contextual factors that contribute to resilience. The findings reveal that although child/youth participants experienced numerous challenges during and after the flood, they had higher than average levels of resilience. High levels of resilience were related to two primary factors– individual factors, specifically peer support, and caregiver factors, namely caregiver psychological support. These findings show that both peer support and caregiver psychological support play a crucial role in strengthening children and youth's resilience following disaster. These findings highlight the importance of utilizing a social-ecological approach to resilience in social work policy and practice which is inclusive of peers and caregivers alike. Abstract: Children and youth are among the most vulnerable to the detrimental effects of disaster due to their unique physical, cognitive and psychological life stage. Despite their increased vulnerability, children and youth also demonstrate resilience when faced with the adverse circumstances of disasters, and can act as important catalysts for change in their families and communities. This article discusses research conducted with eighty-three children and youth (five to seventeen years) who experienced the 2013 flood in Alberta, Canada. A mixed-methods approach was utilised. The Child and Youth Resilience Measure was used to examine the factors that contribute to resilience post-disaster, including individual, care-giver and contextual factors. In-depth qualitative interviews further examined the specific ways in which individual, caregiver and contextual factors contribute to higher levels of resilience. Findings reveal that despite numerous post-flood challenges, children and youth had higher than average levels of resilience. The findings demonstrate that high levels of resilience are associated with individual factors, specifically peer support and caregiver factors, namely caregiver psychological support. We discuss the implications of these findings for social work policy and practice, and for understanding the factors that best support the resiliency processes and overall recovery of children and youth following disaster.